Parental Education and Invention: The Finnish Enigma - Philippe Aghion; Ufuk Akcigit; Ari Hyytinen; Otto Toivanen (Helsinki Graduate School of Economics, 2023)
Why is invention strongly positively correlated with parental income not only in the US but also in Finland which displays low income inequality and high social mobility? Using data on 1.45M Finnish individuals and their parents, we find that: (i) the positive association between parental income and off-spring probability of inventing is greatly reduced when controlling for parental education; (ii) instrumenting for the parents having a MSc-degree using distance to nearest university reveals a large causal effect of parental education on offspring probability of inventing; and (iii) the causal effect of parental education has been markedly weakened by the introduction in the early 1970s of a compre- hensive schooling reform.
Keywords: O31; O35; I25; I26; 330; Education; Inventors; Innovation; Patents; Parents' education